Analisis Mesh Size Untuk Konvergensi Coil Spring Roda Depan Minibus Menggunakan Metode Elemen Hingga - Jagodang Harahap; Teuku Edisah Putra; Arya Rudi Nasution; Veranita Veranita (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2025)
AbstractMesh convergence in finite element analysis is crucial for ensuring simulation accuracy, especially in vehicle coil springs. However, limited studies have evaluated the balance between accuracy and computational efficiency due to mesh size variations. Stress-strain data is obtained from the strain that occurs when driving by installing a strain gauge on the coil spring. This study analyzes the effect of mesh size on stress distribution, deformation, and computation time in the front coil spring of a minibus using FEMAP NX Nastran software. The results show that smaller mesh sizes yield higher stress and deformation values, with a maximum stress of 817 MPa at a 0.1 mesh size and 733 MPa at a 0.6 mesh size. While improving accuracy, finer mesh sizes significantly increase computation time. Therefore, balancing accuracy and computational efficiency is essential for optimizing coil spring design, with further research recommended to determine the optimal mesh size in finite element simulations.Keywords— Mesh Convergence, Finite Element Analysis, Stress Distribution, Computational Efficiency